Performance of The Histamine Level During Tuna Steak Processing - Ginting, Emmya Karina; Siregar, Resmi Rumenta; Masengi, Simson; Napitupulu, Romauli Juliana (Politeknik Ahli Usaha Perikanan, 2024)
This research aims to observe the suitability of tuna processing with the Indonesian National Standards and analyze the increase of histamine levels during the processing steps of steak tuna at tuna processing plant located in Medan, North Sumatra. This research was conduct with observation using a questionnaire. The questionnaire was created referring to the Indonesian National Standards regarding to frozen tuna steak processing steps. Testing for histamine levels was carried out using the ELISA method. Data was analyzed using gap analysis and the increase in histamine levels was analyzed using Microsoft Excel to see the trend of increasing histamin e levels during the tuna fish processing steps. The research results show that the level of suitability of the processing steps at processing plant is 98.37%, with a gap level of 1.73%. This mean that processing of frozen tuna steak products has been carried out well. The histamine at four steps showed that there was increasing of histamine levels from receiving raw materials to the final product up to 800%. The highest increase occurred in the loining proccess to the steak cutting steps which is up to 200%; followed by the steak cutting to the final product increased up to 80%; and receiving raw materials to loining steps increased up to 66,7%. Although the increasing of the histamine was high (up to 800% from the histamine levels of the raw materials), the histamine of the final product was still low (only 2.7 ppm) and still meets the Processing Unit requirements (max 30 ppm), as well as the Indonesian National Standard.